Characteristics of Cement Treated Soil: A Case Study from Soft Bangkok Clay and Red Soil of Nepal - Salisa Chaiyaput; S Manandhar; S Karki; J Ayawanna (International Association of Lowland Technology, 2020)
Soft Bangkok Clay from Thailand and clayey silt of red soil,Nepal have been incorporated for the research as a case studyin order to understand the characteristics. Highly plastic softBangkok Clay and low plastic clayey silt have been confirmedas non-swelling soils through XRD analyses. The peakintensities of red soil from Nepal is more than two times higherthan the intensity of soft Bangkok Clay. Higher water contentand warm temperature form lower intensities in the soft BangkokClay resembling the amorphous state with compared to red soilof Nepal. As a result, the amount of admixture of cement in clayvaries significantly to enhance the adequate strength. Hence,the research has delineated through determining undrainedstrengths treated with cement in different proportions at differentcuring time and checked the stiffness by passing throughultrasonic wave velocity. The specimens were extracted fromthe depths of 3.0 m and 12.0 m soil-cement column formed bydry method in Thailand and in-situ clayey silt from Nepal wastreated with cement. Besides, 20% local poorly graded soil wasadded in the clayey silt and all treated specimens were cured for7, 14 and 28 days. The results confirmed that the Bangkok Clayreceived the highest strength at 13.89% of cement addition for3.0 m depth core and 11.11% of cement treatment received themaximum strength for 12.0 m core cured for 28 days.Conversely, clayey silt from Nepal received the maximumstrengths at 7% cement treatment cured for 28 days.